Efficacy of the Chinese herbal medicine Jintiange capsules in the postoperative treatment of osteoporotic vertebral compression fractures: a systematic review and meta-analysis - Fu, Yongsheng; Wang, Weiguo; Zhao, Minghua; Zhao, Jianpeng; Tan, Mingyue (Frontiers in Medicine, 2023)
In traditional Chinese medicine, Jintiange capsules are frequently used to treat metabolic bone diseases and strengthen bones and tendons. The main component of the Jintiange capsule is bionic tiger bone powder. However, the active ingredients and proteins are derived from other animal bones, with chemical profiles similar to natural tiger bone. This study aimed to explore the efficacy of the Chinese Herbal Medicine Jintiange capsule for postoperative treatment of Osteoporotic Vertebral Compression Fractures (OVCFs).In this systematic review, literature was retrieved using PubMed, Cochrane Library, Chinese National Knowledge Infrastructure, Web of Science, Wanfang Database, Chinese Biomedical Literature Database, and Chinese VIP Database from inception to July 2023. The primary outcome measures are the bone mineral density (BMD) and effective rate. The secondary outcome measures are the visual analog pain score (VAS), Oswestry Disability Index (ODI), Cobb's angle, serum osteocalcin, serum Alkaline Phosphatase, and adverse events. RevMan 5.4 and STATA 17.0 software were used for data analysis.We enrolled randomized controlled trials (RCTs) focusing on 1642 patients in the meta-analysis. The meta-analysis illustrated that the Jintiange capsule remarkably increased the BMD of the lumbar spine (P<0.00001), femoral neck (P=0.0005), and whole body (p=0.01). The subgroup analysis of the Jintiange capsule combination therapy showed that BMD of the lumbar spine and whole body was significantly improved with the Jintiange capsule (P<0.00001). The test for the overall effect showed that the Jintiange capsule was remarkable for the effective rate compared with the control groups (P=0.003). Additionally, the overall effect test showed that the Jintiange capsule decreased VAS and ODI (P < 0.00001), and cobb's angle (P = 0.02), and improved Serum OC and ALP (P < 0.00001) than the controls. Furthermore, the pooled analysis of adverse reactions showed no serious impacts on the treatment of OVCFs.The Jintiange capsule demonstrates high safety and efficacy in the treatment of OVCFs, including increasing BMD, lift effect rate, relieving pain, decreasing ODI, improving cobb's angle, raising the level of serum OC, and decreasing adverse events. Additional research is required to validate the efficacy of the Jintiange capsule for the postoperative treatment of OVCFs.